Work Permit Regulations and Migrants' Labor Market Outcomes - Pamela Qendrai (Institute of Labor Economics (IZA), 2022)
This paper studies how the introduction of a novel residence permit for working purposes – the so-called Blue Card introduced in August 2012 – has affected entry-level wages of non-EU migrants in Germany. The Blue Card was targeted at non-EU university graduates with degrees received or recognized in Germany. It provided immediate residence to students with a working contract that pays above clearly-announced and regularly-updated wage thresholds. We leverage a difference-in-difference approach and unique data on national and international graduates in Germany between 2011-2014. We find that the introduction of the Blue Card increases entry-level wages of non-EU graduates relative to the control group by approximately 2 percent of the pre-treatment entry-level wages. We provide suggestive evidence that these results are not driven by more or better-quality non-EU graduates staying in Germany, but rather because the Blue Card wage threshold acts as a reference point.
Keywords: J60; J61; J63; 330; work permit; foreign students; highly-educated migrants; wages